Efek konsumsi minuman berkarbonasi dan minuman rasa jeruk terhadap pH saliva pada mahasiswa PSPDG Fakultas Kedokteran Universitas Udayana - Lydia Kurnia Purwanti; Ni Kd. Fiora Rena Pertiwi; Putu Ika Anggaraeni (Bali Dental Journal, 2018)
Background: Food consumption pattern influences salivary acidity and can directly cause dental health problems. Sugar and acid containing beverages will alter the salivary pH and make the teeth susceptible to caries and dental erosion. Objective: The aim of this study is to understand the effect of consuming carbonated and orange drinks on subjects’ salivary pH. Methods: Experimental method is used in this study, using pre and posttest control group design comprised 27 subjects divided into 3 groups (A, B and C). Test beverages were carbonated drink, orange drink and plain water as control. Measurement of salivary pH was done before and after intervention at 0 minutes, 5 minutes and 10 minutes. Results: Collected data were analyzed using One-Way ANOVA and Post Hoc tests. There were significant differences of mean salivary pH among these 3 groups at 0 minutes, 5 minutes and 10 minutes (p<0,05). Conclusion: It was concluded that mean value of subjects’ baseline salivary pH was 7,20 – 7,36. Mean value of salivary pH after carbonated drink consumption was found lowest at 0 minutes which was 6,67 and after orange drink consumption also found lowest at 0 minutes which was 6,83.